PENGARUH PENGGUNAAN VITAMIN BATERAI VITTA-Q TERHADAP TEMPERATUR CHARGING DAN BERAT ELEKTROLIT PADA YUASA LEAD ACID BATTERY TIPE LIQUID VENTED 12V 5AH - Wibowo, Indra Angga (Jurnal Nosel, 2014)
The purpose of this research: (1) To investigate the rate of increase in battery temperature during charging using battery charger and weight reduction in Yuasa lead acid battery 12V 5Ah liquid vented type before giving Vitta-Q battery vitamin. (2) To investigate the rate of increase in battery temperature during charging using battery charger and weight reduction in Yuasa lead acid battery 12V 5Ah liquid vented type after giving Vitta-Q battery vitamin. Based on this research can be concluded: (1) The measurement on Yuasa lead acid battery 12V 5Ah liquid vented type before giving Vitta-Q battery vitamin during charging using battery charger resulted the temperature 49 oC and weight of electrolyte 209.5 gr in 230.0 gr electrolytes. (2) The measurement on Yuasa lead acid battery 12V 5Ah liquid vented type after giving 2 ml of Vitta - Q battery vitamin per cell during charging using battery charger resulted the lowest temperature 40.3 oC and weight of electrolyte 216.4 gr in 230.0 gr electrolytes. (3) The measurement on Yuasa lead acid battery 12V 5Ah liquid vented type after giving 3.5 ml of Vitta - Q battery vitamin per cell during charging using battery charger resulted the highest temperature 49.8 oC and weight of electrolyte 208.1 gr in 230.0 gr electrolytes.